The Effect of Increase in NaCl Concentration on Growth and Proline Content of Purple Yam (Dioscorea alata L.) Grown In Vitro - Martin, Andri Fadillah; Azizah, Farroh; Wulandari, Dyah Retno; Ermayanti, Tri Muji (BRIN, 2012)
Tuber of purple yam (Dioscorea alata L.) has been used as an alternative food in some areas in Indonesia. The tuber contains high carbohydrate, low glycemic index and gluten free, therefore, study on genetic improvement of this species is needed to increase the productivity and to find out new cultivars which can be cultivated in marginal lands. This research was aimed to investigate the effect of NaCl concentration on growth and proline content of purple yam grown in vitro. Shoot tips were cultured on MS (Murashige and Skoog) medium supplemented with NaCl at concentrations of 25; 50; 100; 200 and 250 mM. After six weeks in culture, height of shoots, number of nodes, number of leaves, as well as proline content were recorded. The results showed that shoots grown on MS medium supplemented with NaCl at 25 and 50 mM had better growth compared to control. The best medium for its growth was MS containing 50 mM of NaCl. Increase in NaCl level’s resulted in decrease of growth. The LD50 value was obtained at 183 mM of NaCl. The Highest proline concentration was achieved by shoots grown on the medium supplemented with 100 mM of NaCl. This result indicated that purple yam was tolerant to the increase of NaCl concentration up to 100 mM, on MS medium without addition of plant growth regulators.